The Mechanism for Online Publishers to Monetize a Website and Manage the Contextual Advertising - Mohd Rosni, Nor Edlina; Zainal Abidin, Ahmad Izuddin; A. Jamak, Abu Bakar Sedek (Journal of Computing Technologies and Creative Content, 2016)
The evolution of technology and internet (World Wide Web) has brought about many predictions of their possibilities to transform the businesses, education, economy, and social at bigger perspective. With the advent of the internet and ad server in early 1990s, internet has become one of the marketing channels that have been used for advertising purpose. Based on the article stated in Digital Advertising Broke $100 Billion in 2012 it mentioned that “In 2012, web advertising approximately grew about 55.8% in the Middle East and Africa and 38.4% in Eastern Europe while 21.5% and 13.9% for North America and Western Europe”. The latter shows that the users and the advertisers increasingly shift their attention on web applications that as well give the benefits to the publishers to maximize more revenue.This project going to discuss further details the mechanism for publishers to monetize their website and to match the related advertisements with the website contents. Providing these kinds of advertising (contextual) will give a challenge to the publishers to display the advertisement that possibly will be clicked on by the users. Two main objectives will be addressed in these research papers are; to study the best approach for the publishers to maximize the revenues by displaying related advertisement with website and to develop a website prototype that shows important connection between the function of publishers to maintain and manage the website contents and Contextual Ads.Hence, the scope of the study will be discussing on the major player in online advertisement which is publisher; to learn, discover and analyze the theory and concept of online advertisement and contextual advertising from publisher’s perspective.